Association of Vitamin D with CRP as A Diagnostic Marker of Cytokine Storm in COVID-19 Patients - Gul, Samina; Khan, Muhammad Ajmal (International Journal of Human and Health Sciences (IJHHS), 2022)
The novel corona virus disease (COVID-19) outbreak imposed the catastrophic impact on the communities worldwide. Recentevidence suggests that vitamin D is one of the important factors that affects the COVID-19 disease severity and the mortality increased in the vitamin D deficient COVID-19 patients. Since C- reactive protein (CRP)is an indicator of inflammation, an increase in levels of Vitamin D hence leads to the decrease in cytokines which ultimately affects the degree of C reactive proteins in the patients. In this review, we have focusedhere on the association between vitamin D and surrogate marker C- reactive protein (CRP)in cytokine storms in COVID-19 patients. International Journal of Human and Health Sciences Vol. 06 No. 04 Oct’22 Page: 355-361